Nursing and Midwifery Student's Attitudes Toward Vital Signs Monitoring Using an Arabic Version of the V-Scale Instrument and Its Influencing Factors - Mohammad Etoom; Rafi Alnjadat; Eshraq Al Momani; Amer Al-Omari; Murad Al-ta’ani (SAGE Open Nursing)
Introduction Vital signs monitoring is a common task for nursing and midwifery students during their clinical rotation. Therefore, it is important to evaluate the students’ attitudes toward this skill. Objective To evaluate the attitudes of nursing and midwifery students toward vital sign monitoring and identify the key factors that influence them. Methods A descriptive, correlational, cross-sectional research design was employed, utilizing an online self-administered questionnaire. The study participants were selected through a simple random sampling method. The translated V-scale instrument was used to assess the nursing students’ attitudes toward vital sign monitoring. Descriptive statistics were computed, and multivariate linear regression was employed for data analysis. Results The total number of participants in this study was 215 students. The study found that the mean score for students’ attitudes regarding vital sign monitoring was 3.17 ( SD  = 0.37). Notably, the communication subscale received the highest mean score of 4.16 ( SD  = 0.56). The workload subscale, on the other hand, had the lowest mean score, 2.37 ( SD  = 0.76). The backward stepwise regression revealed that academic programs such as midwifery (β  =  .146, t  = 2.17, P  < .05) and grade point average (GPA) (β  =  .172, t  = 2.55, P  < .05) are statistically significant predictors for student's attitudes toward vital signs monitoring. The adjusted R 2 of .038 suggested that approximately 3.8% of the variance in attitude level toward vital signs monitoring was explained by the academic program of midwifery and GPA ( R 2  = .047, adj. R 2  = .038, F (2, 212) = 5.271, P  < .01). Conclusion The participating students in this research exhibited moderate attitudes toward vital sign monitoring. The most positive attitude was in the communication subscale, while the most negative attitude was in the workload subscale. We identified academic program variables like midwifery and GPA as significant predictors of students’ attitudes toward vital signs monitoring.